Modelling of power diode for computer-aided analysis of power electronic circuits - Pan, Su Zhen (2009)
The objective of this project is to develop power diode models for use in circuit simulation. The models have to predict the experimental results as realistically as possible. In this project, two power diode models have been proposed using analytical and one-dimensional hybrid modelling approaches. Both of them are based on an important modification to the charge-control equation to take into account the storage charges in the diode. The models also incorporate a new charge-dependent resistance equation to account for the diode's mid-region conductivity modulation characteristics. The difference between the analytical and hybrid model is that the storage charges in the mid-region and the charge-dependent resistance of the mid-region are calculated by analytical equations in the former, and by finite difference algorithm in the latter.